Study on the new polyurethane material suitable for foaming in water. (7th November 2022) - Li, Manjun; Fang, Hongyuan; Zhang, Chao; Du, Mingrui; Wang, Fuming
Highlights: Foaming in water will affect the internal cell structure of polyurethane materials to a certain extent. Compared with other polyurethanes, the polyurethane modified in this test has better foaming effect in water. The mechanical strength of polyurethane specimens decreased obviously in the early stage of soaking in water, and tended to be stable after 15 h. Different stress directions have different effects on the mechanical strength of polyurethane specimens. Abstract: Two-component polyurethane has been widely used in various types of engineering. In this work, polyurethane samples with different foaming ratios were obtained by adjusting the ratio of each component and foaming in water. By studying the morphology and mechanical properties of these specimens, the polyurethane with foaming ratio of 16 was selected as the most suitable polyurethane for foaming in water, and the mechanical properties of this material were deeply studied. The results show that the compressive, tensile and bending strengths of polyurethane increase with the increase of density and decrease with the increase of soaking time. In addition, compared with the force along the growth direction, when the polyurethane specimens are subjected to the force orthogonal to the growth direction, their compressive strength decrease, while their tensile strength and bending strength increase.